Conductivity and Surface Passivation Properties of Boron‐Doped Poly‐Silicon Passivated Contacts for c‐Si Solar Cells. Issue 10 (5th October 2018) - Morisset, Audrey; Cabal, Raphaël; Grange, Bernadette; Marchat, Clément; Alvarez, José; Gueunier‐Farret, Marie‐Estelle; Dubois, Sébastien; Kleider, Jean‐Paul
Abstract : Passivating the contacts of crystalline silicon (c‐Si) solar cells with a poly‐crystalline silicon (poly Si) layer on top of a thin silicon oxide (SiOx ) film are currently of growing interest to reduce recombination at the interface between the metal electrode and the c‐Si substrate. This study focuses on the development of boron‐doped poly‐Si/SiOx structure to obtain a hole selective passivated contact with a reduced recombination current density and a high photo‐voltage potential. The poly‐Si layer is obtained by depositing a hydrogen‐rich amorphous silicon layer by plasma enhanced chemical vapor deposition (PECVD) exposed then to an annealing step. Using the PECVD route enables to single side deposit the poly Si layer, however, a blistering of the layer appears due to its high hydrogen content, which leads to the degradation of the poly‐Si layer after annealing. In this study, the deposition temperature and gas flow ratio used during PECVD step are optimized to obtain blister‐free poly‐Si layer. The stability of the surface passivation properties over time is shown to depend on the blister density. The surface passivation properties are further improved thanks to a post process hydrogenation step. As a result, a mean implied photo‐voltage value of 714 mV is obtained. Abstract : Boron‐doped polycrystalline silicon (poly‐Si) layer on a thin silicon oxide layer as a passivating structure for c‐Si solar cells is studied. The deposition conditions are optimized to obtain blister‐free poly‐Si layer. The surface passivation properties of the resulting passivating structure are evaluated in accordance with the blister density and the annealing temperature. Conductive‐AFM measurements are performed to study the charge carrier transport in the structure.